Concise review: Emerging concepts in clinical targeting of cancer stem cells - Rasheed, Zeshaan A. (2011)
Cancer stem cells (CSCs) are functionally defined by their ability to self-renew and recapitulate tumors in the ectopic setting. They have been identified in a growing number of human malignancies and their association with poor clinical outcomes has suggested that they are a major factor in dictating clinical outcomes. Moreover, recent studies have demonstrated that CSCs may display other functional attributes, such as drug resistance and invasion and migration, that implicates a broad role in clinical oncology spanning initial tumor formation, relapse following treatment, and disease progression. Although our knowledge regarding the basic biology of CSCs continues to improve, a major issue remains proof that they are clinically relevant, and translation of the CSC hypothesis from the lab to the clinic is of paramount importance. We will review current evidence supporting the role of CSCs in clinical oncology and discuss potential barriers and strategies in designing trials examining CSC-targeting agents.